Polydatin ameliorates early brain injury after subarachnoid hemorrhage through up-regulating SIRT1 to suppress endoplasmic reticulum stress - Han, Yuwei; Hao, Guangzhi; Han, Song; Zhu, Tingzhun; Dong, Yushu; Chen, Ligang; Yang, Xinyu; Li, Xiaoming; Jin, Hai; Liang, Guobiao (Frontiers in Pharmacology, 2024)
Objective: This study aims to investigate the inhibitory effect of Polydatin (PD) on endoplasmic reticulum (ER) stress following subarachnoid hemorrhage (SAH) and to elucidate the underlying mechanisms.: A standard intravascular puncture model was established to mimic SAH in mice. Neurological functions were assessed using neurological scoring, Grip test, and Morris water maze. Brain edema and Evans blue extravasation were measured to evaluate blood-brain barrier permeability. Western blot and quantitative real-time polymerase chain reaction (PCR) analyses were performed to examine protein and mRNA expressions related to ER stress. Terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining was used to detect cell apoptosis, and transmission electron microscopy was used to observe the ultrastructure of the endoplasmic reticulum. Results: The results indicated that PD significantly reduced brain edema and Evans blue extravasation after SAH, improving neurological function. Compared to the SAH group, the expression levels of ER stress-related proteins including glucose-regulated protein 78 (GRP78), phosphorylated protein kinase R-like endoplasmic reticulum kinase (p-PERK), phosphorylated eukaryotic initiation factor 2α (p-eIF2α), activating transcription factor 4 (ATF4), and C/EBP homologous protein (CHOP), were significantly lower in the PD-treated group. Moreover, PD significantly enhances the protein expression of Sirtuin 1 (SIRT1). Validation with sh-SIRT1 confirmed the critical role of SIRT1 in ER stress, with PD's inhibitory effect on ER stress being dependent on SIRT1 expression. Additionally, PD attenuated ER stressmediated neuronal apoptosis and SAH-induced ferroptosis through upregulation of SIRT1. Conclusion: PD alleviates ER stress following SAH by upregulating SIRT1 expression, thereby mitigating early brain injury. The protective effects of PD are mediated through SIRT1, which inhibits ER stress and reduces neuronal apoptosis and ferroptosis.